Effect of Tube Thickness Configuration of Two Segments Circular Crash Box on Its Crashworthiness Performance - Muhammad Vendy Hermawan; Moch. Agus Choiron; Anindito Purnowidodo; Winarto Winarto (Universitas Muhammadiyah Magelang, 2025)
This study aims to investigate the effect of tube configuration with different bottom fixation components on the energy absorption of a two-segment crash box. The circular tube thickness configuration has two thickness levels, half of the length of the tube has thicker walls (t2), and the other half has thinner walls (t1). The t1 values ”‹”‹are 1, 1.5, 2 and 2.5 mm while t2 is constant, 3 mm. Finite element analysis using ANSYS WORKBENCH was performed for the axial load model. The bottom fixation component uses Cutting Die Model (CDM) and Flat Model (FM). Sixteen crash box models were run to provide the effect of two tube thickness configurations and CDM-FM fixation components. The material of the circular tubes is Aluminum 6063 with a Bilinear Hardening Model assumption. Crashworthiness performance indicators were observed based on the values ”‹”‹of Energy Absorber (EA), Specific Energy Absorber (SEA), initial peak force (Fmax), and Crash Force Efficiency (CFE). The results show that the CDM model has the lowest Fmax value, due to the use of the die, which stimulates easier initial folding in the tube end area. The CDM model also has better SEA and CFE values. According to the results obtained from computer simulations, the CDM-t2t1 model with t1=1mm exhibited the highest Specific Energy Absorption (SEA) of 67.93 kJ. On the other hand, this same crash box model provided the smallest Fmax of 205.88 kN and the highest CFE value of 0.69. From these results, it can be concluded that this model provides the best crashworthiness performance.